Mutation of von Hippel-Lindau tumour suppressor and human cardiopulmonary physiology. - Smith, T; Brooks, J; Balanos, G; Lappin, T; Layton, D; Leedham, D; Liu, C; Maxwell, P; McMullin, M; McNamara, C; Percy, M; Pugh, C; et al. (2006)
BACKGROUND: The von Hippel-Lindau tumour suppressor protein-hypoxia-inducible factor (VHL-HIF) pathway has attracted widespread medical interest as a transcriptional system controlling cellular responses to hypoxia, yet insights into its role in systemic human physiology remain limited. Chuvash polycythaemia has recently been defined as a new form of VHL-associated disease, distinct from the classical VHL-associated inherited cancer syndrome, in which germline homozygosity for a hypomorphic VHL allele causes a generalised abnormality in VHL-HIF signalling. Affected individuals thus provide a unique opportunity to explore the integrative physiology of this signalling pathway. This study investigated patients with Chuvash polycythaemia in order to analyse the role of the VHL-HIF pathway in systemic human cardiopulmonary physiology. METHODS AND FINDINGS: Twelve participants, three with Chuvash polycythaemia and nine controls, were studied at baseline and during hypoxia. Participants breathed through a mouthpiece, and pulmonary ventilation was measured while pulmonary vascular tone was assessed echocardiographically. Individuals with Chuvash polycythaemia were found to have striking abnormalities in respiratory and pulmonary vascular regulation. Basal ventilation and pulmonary vascular tone were elevated, and ventilatory, pulmonary vasoconstrictive, and heart rate responses to acute hypoxia were greatly increased. CONCLUSIONS: The features observed in this small group of patients with Chuvash polycythaemia are highly characteristic of those associated with acclimatisation to the hypoxia of high altitude. More generally, the phenotype associated with Chuvash polycythaemia demonstrates that VHL plays a major role in the underlying calibration and homeostasis of the respiratory and cardiovascular systems, most likely through its central role in the regulation of HIF.